Cardiometabolic risk factors in patients with type 2 diabetes and sarcopenia - Yu. G. Samoilova; M. V. Matveeva; E. A. Khoroshunova; D. V. Podchinenova; L. L. Maksimova; G. G. Gorbach; A. B. Trivozhenko; V. A. Avkhimenko (Кардиоваскулярная терапия и профилактика, 2024)
Aim. To analyze risk factors for sarcopenia in atherosclerosis involvement of target organs in patients with type 2 diabetes (T2D).Material and methods. The study included 84 patients with T2D, divided into groups according to the 2019 criteria of the European Working Group on Sarcopenia in Older People (EWGSOP2). All patients were surveyed using a 36-item short-form health survey (SF-36), Sarcopenia and Quality of Life (SarQoL), Strength, Assistance with walking, Rise from a chair, Climb stairs and Falls (SARC-F), grip test, 4-meter walk test, bioelectrical impedance analysis, 24-hour blood pressure monitoring and cardiac ultrasound. Differences were considered significant at p<0,05.Results. Patients with sarcopenia have lower levels of fat, muscle, cell mass, appendicular mass index, fluid, protein, and minerals. In the group with sarcopenia, higher levels of total cholesterol, low-density lipoprotein cholesterol, glycated hemoglobin, and hypocalcemia were detected. Triglyceride levels were high in those with presarcopenia. In the same group, unstable blood pressure, increased myocardial mass and severe lower limb atherosclerosis were recorded.Conclusion. Sarcopenia is one of the important medical and social problems and is accompanied by unfavorable outcomes. The combination of sarcopenia and T2D can contribute to the rapid development of macro- and microangiopathy and increase the cardiovascular risk.